EVALUASI ATAS SURAT PERMINTAAN PENJELASAN ATAS DATA DAN/ATAU KETERANGAN (SP2DK) YANG DITERIMA CV SURYA MANDIRI TAHUN 2023 - hanifah, hanifah; Ridhawati, Rakhmi (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to determine the evaluation of CV. Surya Mandiri responses regarding Letter of Request for Explanation of Data and/or Information (SP2DK) Number: S-1035/P2DK/KPP.2910/2023 dated August 10 2023 issued by the Tax Service Office (KPP) Pratama Banjarmasin. The method used in this research is descriptive qualitative, with this method the author can find out the extent of the description of the response evaluation process to the Letter of Request for Explanation of Data and/or Information (SP2DK) received by CV. Surya Mandiri in 2023. The results of this research indicate that CV. Surya Mandiri has answered the Letter Requesting Explanation of Data and/or Information (SP2DK) accompanied by evidence, and KPP Pratama Banjarmasin stated that this was true by publishing the Minutes on September 22 2023, so that there is tax that still needs to be paid.